Exploring nurses' experiences of recommended patient care: a descriptive phenomenological study - Azam Faraji; Amir Jalali; Alireza Khatony; Rostam Jalali (BMC, 2024)
Abstract Background Caring for recommended patients creates work and emotional challenges for nurses. Nurses are obligated to provide care regardless of the patient's situation. Therefore, knowing the experiences of nurses in dealing with recommended patients in order to provide quality and effective care can be the basis for increasing patient satisfaction. The present study was conducted aimed to explain nurses' experiences of caring for recommended patients. Methods This was a qualitative study with descriptive phenomenological approach. Participants were 12 nurses working in different wards of hospitals affiliated to Kermanshah University of Medical Sciences, selected by purposive sampling method with maximum diversity. The data collected using semi-structured interviews in face-to-face and audio-recorded methods. MAXQDA 2020 software was used for data management. The analysis of the data was done using the Colaizzi's 7-step method. In order to verify the trustworthiness of the data, Lincoln and Guba criteria were used. Results After continuous data analysis, 110 initial codes were extracted. These codes emerged in 18 sub-themes and 6 main themes including: catastrophe, be in decline, be in progress, discrimination, work overload, and poor prognosis. Conclusions The results showed information about the presence of recommended patients in the hospital, which can have consequences for patients and nurses. Therefore, it is advised that nurses provide standard care and avoid any kind of discrimination against all patients regardless of whether the patient is recommended or not.